Basque in education : in the Basque Autonomous Community - Gardner, Nikolas; Euskadi. Argitalpen Zerbitzu Nagusia; Euskadi. Hezkuntza, Unibertsitate eta Ikerketa Saila; Euskadi. Hezkuntza, Unibertsitate eta Ikerketa Saila. Euskara Zerbitzua (Vitoria-Gasteiz : Eusko Jaurlaritzaren Argitalpen Zerbitzu Nagusia, 2000)
Basque has been marginally present in education for well over a century but the Spanish constitution of 1978 and subsequent legislation have provided the opportunity for a remarkable expansion in the usu of Basque Autonomous Community (Spain). This expansion has aroused the interest of academics and minority language loyalists worldwide. As a result, since its inception at the beginning of the nineteen eighties, the Department of Educaticon, Universities and Research of the Basque Government has received numerous requests for information on the inplantation of Basque alongside Spanish in the local education system. This book gathers together the answers to the most common questions, at the same time setting them in the broader context of the ongoing language planning initiative for Basque, which can be traced as far back as the fifties.
Keywords: Hezkuntza elebiduna -- Euskadi (Autonomia Erkidegoa); Hizkuntza Politika -- -Euskadi (Autonomia Erkidegoa); Monografiak; Baliabide digitalak